2004
DOI: 10.1093/brain/awh133
|View full text |Cite
|
Sign up to set email alerts
|

Hemispheric asymmetries for kinematic and positional aspects of reaching

Abstract: Kinematic analyses of reaching have suggested that the left hemisphere is dominant for controlling the open loop component of the movement, which is more dependent on motor programmes; and the right hemisphere is dominant for controlling the closed loop component, which is more dependent on sensory feedback. This open and closed loop hypothesis of hemispheric asymmetry would also predict that advance planning should be dependent on the left hemisphere, and on-line response modification, which defines closed lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

14
167
2
6

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 190 publications
(189 citation statements)
references
References 57 publications
14
167
2
6
Order By: Relevance
“…In fact, Healey et al described similar distinctions in dominant and nondominant arm use for a wide range of tasks across a large number of subjects [2]. The dynamic dominance model has recently been supported in studies of righthanded stroke patients that reveal deficits in the ipsilesional arm, the quality of which tend to vary with the side of the lesion [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. The ipsilesional arm of these patients tends to show deficits in trajectory control following lefthemisphere damage and positional control following righthemisphere damage.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…In fact, Healey et al described similar distinctions in dominant and nondominant arm use for a wide range of tasks across a large number of subjects [2]. The dynamic dominance model has recently been supported in studies of righthanded stroke patients that reveal deficits in the ipsilesional arm, the quality of which tend to vary with the side of the lesion [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. The ipsilesional arm of these patients tends to show deficits in trajectory control following lefthemisphere damage and positional control following righthemisphere damage.…”
Section: Introductionmentioning
confidence: 90%
“…In fact, both animal studies [18][19][20] and human studies [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] have revealed that unilateral brain damage can produce significant ipsilesional motor deficits. Studies in chronic stroke patients have reported performance deficiencies on the Purdue Pegboard Test [21], the JebsenTaylor Hand Function Test [22], as well as other tests that simulate activities of daily living (ADL) [4,10,[13][14]. In addition, significant ipsilesional deficits in movement coordination and accuracy have been revealed with the use of motion capture systems [3,[10][11][12]15,17].…”
Section: Introductionmentioning
confidence: 99%
“…Besides severe language dysfunctions, patients with left hemispheric injuries tend to demonstrate a greater frequency of apraxias 4,5 . Motor activities that require planning are more related to the left hemisphere and are therefore more aff ected after left hemispheric injuries 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Motor activities that require planning are more related to the left hemisphere and are therefore more aff ected after left hemispheric injuries 4 . As the majority of activities of daily living involve complex motor sequences, it is possible to suppose that performance of these activities will be more aff ected in patients with left hemispheric injuries, especially because of the alterations in motor responses observed after CVA (hemiparesis), therefore, part of the movement sequence would need to be reprogrammed for activities of daily living.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation